Study of patient satisfaction from nursing care and behaviors in Shahrekord ‎hospitals - neda parvin; azam alavi; batool tahmasbi (Journal of Holistic Nursing and Midwifery)
Introduction: Gaining patient satisfaction is among important goals in health care system. ‎Nurses due to the type of their profession, have an essential role in providing satisfaction to ‎patients hospitalized in treatment centers especially hospitals. An efficient health care system ‎can only reach its mission, maintaining public health, through providing satisfactory care and it ‎can be assessed by assessing care provided.‎